Fabric covering matter: language and materiality on the fiction of Jorge Eduardo Eielson - Medina García, Pamela (Anales de Literatura Hispanoamericana, 2022)
The objective of this paper is to identify the way in which language has become a persistent concern in the works of the Peruvian artist Jorge Eielson (1914-2006), it is this concern that bestowed an interdisciplinary nature to his works. Specifically, the conscience of a language travels and links the disciplines developed by the artist like poetry, novels or fine arts. It is precisely in the last two where we will focus our analysis, the novels El cuerpo de Giulia-no (1971) and Primera muerte de María (1988), and the matter painting series Paisaje infinito de la costa del Perú (1960-1980). In order to do this, we will work in a two-step interdisciplinary approach. In the First, we will tackle both the narrative and the philosophical aspects in El cuerpo de Giulia-no to establish that the characters built by Eielson are subjects of the language. Second, we will confront the dialogues of Primera muerte de María with the fine arts so we can question both the writing in general and the representation of a language. Our research will allow us to conclude that Jorge Eielson is an artist aware of the language, and it is from here and from his self-reflective nature, that he braces and diversifies the written and matter painted work.
Keywords: language; matter; novel; Eielson; interdisciplinarity